Pengaruh Profitabilitas, Leverage, dan Kepemilikan Manajemen pada Pengungkapan CSR dengan Ukuran Perusahaan sebagai Variabel Kontrol - Ariswari, Putu Mira Ayu; Eka Damayanthi, I Gst Ayu (E-Jurnal Akuntansi, 2019)
The form of the company's responsibility for its environment is by disclosing CSR. Disclosure of CSR is required by law but there are still companies that do not disclose CSR. The purpose of this study was to determine the effect of profitability, leverage, and management ownership on CSR disclosure with company size as a control variable. The number of samples is 48 observations using the nonprobability sampling method. The data collection method used is a nonparticipant observation method. The data analysis technique is multiple linear regression analysis. This study concludes that profitability and management ownership have a positive and significant effect. Meanwhile, leverage does not have aeffect on disclosure of CSR. The results of this study form the basis for management in increasing CSR disclosure for the sustainability of the company. Keywords : Profitability; Leverage; Management Ownership; Disclosure Of Corporate Social Responsibility.